NEPHROPROTECTIVE ROLE OF ZINC AGAINST THE AMMONIUM SULFATE TOXICITY IN MALE ALBINO RATS - TEKURI, SIVA KUMAR; RANI AMURU, SHOBHA; BASSAIAHGARI, PURUSOTHAM; GALI, YUVARANJANI; PABBARAJU, NEERAJA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Intention of the present study is to investigate the protective role of zinc against ammonium sulfate (AS) toxicity in renal tissue by evaluating certain biochemical activities of albino rats. Methods: Rats were divided into four groups, namely control, ammonia, zinc, and ammonia + zinc. Rats were exposed to AS (18.3 mg/kg body weight) or zinc chloride (4 mg/kg body weight) or both through intraperitoneally for 7-day experimentation with 24-h time interval. Results: AS-administered rats showed significant increased levels of ammonia, urea, glutamine, glutamine synthetase, free amino acids, and lactate dehydrogenase and decreased levels of total proteins, pyruvate, succinate dehydrogenases, malate dehydrogenase, and biochemical activities when compared with control. Supplementation of zinc mitigated AS-induced oxidative stress and restored all the biochemical parameter activities. Zinc administered to normal rats did not exhibit any significant changes in any of the parameters studied. Conclusion: From the study, it concluded that zinc cotreatment with AS has effectively recovered the mitochondrial enzyme activities and ammonia metabolic biochemical parameters in renal tissue of rat treated with AS.